Analisis Pengaruh Kompetensi, Motivasi, Sarana Prasarana Dan Disiplin Terhadap Kinerja Awak Transportasi Sungai Di Kabupaten Blitar Dengan Kabupaten Tulungagung - Adenanthera Lesmana Dewa; Rizqi Candra Noviasari; Lisda Rahmasari (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2021)
This research is motivated by the problems that often arise in the river transportation of Blitar Regency and Tulungagung Regency, namely the performance of transportation crews caused by lack of infrastructure and discipline that is often violated. So that there are often problems with the performance of transportation crews such as crossing delays, lack of lighting and ship conditions. Through this research, it is expected to obtain results that illustrate that the performance of river transportation crews is influenced by factors of competence, motivation, infrastructure and discipline. This study aims to determine the competence, motivation, infrastructure and discipline on the performance of river transportation crews. The population in this study were passengers and the sample of this study was 100 respondents.sampling technique is nonprobability sampling with the type of sampling, namely incidental sampling. Analysis of the data used in this study is descriptive analysis and quantitative analysis, the data were analyzed using multiple linear regression analysis with the help of (software) Statistical Package For Social Science (SPSS) version 24. The results of the study by partially testing the t-test hypothesis showed that competence, motivation, infrastructure and discipline have a positive and significant effect on the performance of the transportation crew.